Ultrafast Dynamics of Plasmon-Mediated Charge Transfer in Ag@CeO(2) Studied by Free Electron Laser Time-Resolved X-ray Absorption Spectroscopy - Pelli Cresi, Jacopo Stefano (Nano Lett, 2021)
[Image: see text] Expanding the activity of wide bandgap semiconductors from the UV into the visible range has become a central goal for their application in green solar photocatalysis. The hybrid plasmonic/semiconductor system, based on silver nanoparticles (Ag NPs) embedded in a film of CeO(2), is an example of a functional material developed with this aim. In this work, we take advantage of the chemical sensitivity of free electron laser (FEL) time-resolved soft X-ray absorption spectroscopy (TRXAS) to investigate the electron transfer process from the Ag NPs to the CeO(2) film generated by the NPs plasmonic resonance photoexcitation. Ultrafast changes (<200 fs) of the Ce N(4,5) absorption edge allowed us to conclude that the excited Ag NPs transfer electrons to the Ce atoms of the CeO(2) film through a highly efficient electron-based mechanism. These results demonstrate the potential of FEL-based TRXAS measurements for the characterization of energy transfer in novel hybrid plasmonic/semiconductor materials.